KH. MUHAJIRIN AMSAR CONTRIBUTION ON LEGAL HADITH INTERPRETATION - Hakim, Masykur (Ar Raniry : International Journal of Islamic Studies, 2015)
The word ‘contribution’ is originally derived from English word which means to help or donations, for example “His contribution to art literature was very great, which meansa very large contribution to the literature.Or a meaningful contribution to charity which equal understanding to donations to charity.Furthermore, etymologically speaking the word ‘sharh’ (interpretation) is derived from the Arabic sharaha which means‘to explain’, ‘to open’, ‘to pave’. And too, the word ‘sharh’ is usually used to describe the meaning of the hadith, while the word ‘tafsir’ is usually used to explain the meaning of the Qur'an. For the impelementation, the word tafsiris exclusively concerning with the interpretationof the qur'anic meaning. While sharh, relies on hadith interpretation, its content, conclusion (istinbath) for bothlegalormoralof the Prophet’s words, or explaining other disciplines.